New opportunities for biomarkers in cardiovascular risk stratification. Resolution of Advisory board - О. M. Drapkina; A. V. on behalf of the working group Kontsevaya (Российский кардиологический журнал)
Early detection of people with a high-risk of developing cardiovascular diseases is a key point of the prevention strategy. The existing risk scales have a number of limitations: insufficient accuracy for an individual or the appearance of a “residual risk”. Existing approaches to improving the accuracy of risk prediction include the use of biomarkers. Troponin I is promising, which has proven its prognostic value in healthy and asymptomatic individuals at the population level. For example, the BiomarCARE study with the participation of 74 thousand people from 5 countries showed an association of increased troponin I concentration and the frequency of cardiovascular events and overall mortality. Similar results were obtained in other cohorts. The simulation results indicate the potential economic feasibility of using troponin I for the purpose of risk stratification. The first pilot Russian study was conducted, which made it possible to describe the population distribution of troponin levels. It confirmed the prognostic significance of the biomarker in relation to the development of cardiovascular outcomes in men in the Russian population. Further studies on large cohorts are needed to clarify the results of the pilot project.